Predictors for Visual Outcomes in Eye Injuries with Intraocular Foreign Body - Ratanapakorn, Tanapat (Clin Ophthalmol, 2021)
OBJECTIVE: To study the visual outcomes and identify the predictive factors for visual outcomes in patients with eye injuries and retained intraocular foreign bodies (IOFBs). PATIENTS AND METHODS: The medical records of 359 consecutive patients with eye injuries and retained IOFBs were retrospectively reviewed during 2009–2018. Demographic data, clinical findings, treatment and visual outcomes were studied. Univariate and multivariate analyses were used to identify the predictive factors. RESULTS: Most of the patients were male and the average age was 36.4 years old. The three most common causes of eye injuries were grass trimming (25.07%), chiseling (23.12%) and hammering (13.93%). Most of the patients (79.39%) presented with poor initial best-corrected visual acuity (BCVA) (<3/60). Pars plana vitrectomy with IOFB removal was done in 273 eyes (76.04%). After treatment, eyes with poor BCVA (<3/60) decreased from 79.39% to 62.95% and eyes with good BCVA (≥3/60) increased from 20.61% to 37.05%. Poor initial best-corrected visual acuity (odds ratio 23.39, P<0.001), rhegmatogenous retinal detachment (odds ratio 9.91, P<0.001) and the presence of infectious endophthalmitis (odds ratio 2.06, P=0.02) were statistically significant predictive factors for poor visual outcome. CONCLUSION: Most patients with eye injuries and IOFBs usually have poor final BCVA. Poor presenting BCVA, retinal detachment and endophthalmitis are significant predictive factors for poor visual outcomes. These factors can be used to inform the visual prognosis and plan prompt surgical intervention for the patients. Causes of IOFBs were mostly work-related and could be preventable. Education and activation of using appropriate protective safety glasses during work are necessary to avoid serious eye injuries and blindness.